Efficacy of opioid underdosing in ovariosalpingohisterectomy of obese brachycephalic canine patient: Case report - Alves santos, Rosangela; Ferreira, Vinícia Carvalho Dourado (Pubvet, 2023)
This work aimed to report the anesthetic management and pain control in an obese Pug dog patient, submitted to OSH through the use of opioids in a dose calculated based on the estimated weight for the breed, not on the animal’s actual weight. All drugs used in the MPA and anesthetic plan were calculated based on the estimated or ideal weight for the animal’s size, which would be 8 kg, and not based on the actual weight at the time of the procedure, that being 11 kg. Underdosage was used to minimize the chances of adverse effects due to the fact that the patient was brachycephalic. It can be concluded from this work that the entire protocol used with a dose lower than what should be used for the patient’s actual weight was very effective and satisfactory, guaranteeing intense sedation, analgesia and tranquility during the procedure, and requiring a lesser amount of drugs.